Coherent Land Policy and Land Value - Krajewska, Małgorzata; Pawłowski, Krzysztof (Geomatics and Environmental Engineering, 2019)
The present article is an attempt at to prove the thesis that the accurate selection of land use in a local spatial development plan carries over to the behaviours of investors and has a positive influence on the value of land affected by noise nuisance neighbouring an airport ‑ i.e. it does not depreciate it. To this aim, a case study of transaction prices of non-developed land located near the Bydgoszcz airport ‑ Szwederowo was carried out. In its region, two study areas were selected: I ‑ with a noise level of 55‑60 dB and II ‑ with a noise level not exceeding 55 dB, and next, the market of land zoned for services-related and services-technical development, parking lots, depots, and warehouses in these areas was diagnosed. Resources of the strategic noise map (SNM) were used in the research. The research period covered years 2016‑2018. The studies show that the location of a real property in an impact area of airport noise was not an obstacle and did not limit market turnover of real property which remained under the unfavourable influence of this factor. The reason behind the demand is the shrewd introduction of functions in the local plan in the area of increased noise levels as an expression of coherent land use planning. The article addresses the need for the real estate market for help in planning, decision-making and implementation activities in the field of spatial and real estate management.